STUDIES ON INFLUENCE OF BIOFERTILIZERS AND BIOREGULATORS ON FLOWERING, YIELD AND FRUIT QUALITY OF STRAWBERRY CV. SWEET CHARLIE - Singh, AKATH; Singh, J.N. (Annals of Agricultural Research, 2014)
Experiment was conducted to study the response of biofertilizers and bioregulators on strawberry crops. Results indicated that dual inoculation of Azotobactor and Azospirillum with 60 kg nitrogen/ha in conjunction with 100 ppm GA3 proved most effective in increasing fruit set, early flowering, yield and also have a significant improvement in fruit quality i.e. berry size, weight and volume. The maximum TTS, total sugar and ascorbic acid content were obtained with the same treatment combination, however, the effect on acidity and TSS/acid ratio was found to be non-significant.